Pengembangan Aplikasi E-Raport Berbasis Android di Sekolah Dasar Darmawati Arief - Aries Saifudin; Deni Pratama Setia Budi; Irvan Hubbie Iswara; Muhammad Rifai (OKTAL : Jurnal Ilmu Komputer dan Sains, 2024)
The learning outcome is an evaluation of students' understanding of the material throughout one semester. Teachers often face challenges in manually filling in report card grades at Darmawati Arief Private Elementary School. Therefore, a report card application is needed to expedite the process and minimize errors in grade processing. This research utilizes the Research and Development (R&D) method with Java and PHP programming languages and MySQL database. This E-Report application allows 5 users (admin, principal, homeroom teacher, subject teacher, student guardian) to access and monitor students' grades flexibly.